Analisis Pengaruh Mekanisme Corporate Governance terhadap Nilai Perusahaan: Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2019-2023 - Ardelia Dwi Permatasari; Sugeng Wahyudi (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to examine the effect of independent commissioners, audit committees, managerial ownership, and institutional ownership on firm value (Tobin’s Q). Independent commissioners are measured by the number of independent commissioner members, audit committees are measured by the number of audit committee members, managerial ownership is measured by the number of management shares divided by the total outstanding shares, institutional ownership is measured by the number of institutional shares divided by the total outstanding shares, and firm value is measured by Tobin’s Q.The population of this study consists of manufacturing companies in the diversified industry sector listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling technique used purposive sampling, resulting in a sample of 63 manufacturing companies. Research data were obtained from the annual reports of the sampled companies accessed through their official websites and the official website of the Indonesia Stock Exchange. The analysis method employed is panel data regression using Stata 17.The results indicate that the number of independent commissioner members has a significant positive effect on firm value (Tobin’s Q). The audit committee has no effect on firm value (Tobin’s Q). Managerial ownership has no effect on firm value (Tobin’s Q). Institutional ownership has no effect on firm value (Tobin’s Q).